Knowledge of Sexually Transmitted Infections among Deaf Teenagers at SLB YRTRW Surakarta - Huda, Zakaria Nuril; Herry Widyastono; Sri Yamtinah (Proceeding of International Conference on Special Education in South East Asia Region, 2023)
This research is a quantitative study that aims to determine the level of knowledge of teenage deaf students about Sexually Transmitted Infections (STIs). It is a preliminary study that will be followed by a developmental study. The population and sample of this study are 24 teenage deaf students at SLB YRTRW Surakarta, selected using a saturated sampling technique. The data analysis technique used in this research is descriptive statistics. Data collection involves a test to gather information on the knowledge of deaf students about STIs. The results of this study indicate that the majority of the sample were male. Only 6 students or around 17% of the total sample had very good or good knowledge, while 17% had adequate knowledge and 63% had poor knowledge. The number of students with very poor knowledge was only 3% of the total sample.